A comparative study on exergetic, exergoeconomic and exergoenvironmental assessments of two internal auto-cascade refrigeration cycles. (25th July 2017) - Boyaghchi, Fateme Ahmadi; Asgari, Sahar
Highlights: Comparative study is performed for two internal auto-cascade refrigeration systems. Environmental impact and cost rates improve 6.6% and 10.6% by applying system 2. m ̇ 1 with 21.52% improvement of B ̇ P, tot has a substantial effect between two systems. Minimum values of design parameters provide better performance for system 2. Abstract: This research makes a comparative study of an internal auto-cascade refrigeration system (IACRS), i.e. system 1, and a novel ejector enhanced IACRS, or system 2, employing a pressure-constant ejector at the entrance of the phase separator based on exergy, exergoeconomic and exergoenvironmental analyses. R600 is used as a convenient refrigerant in the proposed systems. Compressor mass flow rate ( m ̇ 1 ), condenser inlet temperature (T3 ), refrigeration evaporator inlet temperature (T6 ) and freezer evaporator inlet temperature (T11 ) are chosen as substantial design parameters to evaluate the performance of both proposed systems. The simulation and comparative study show that at all ranges of selected parameters, the average energy and exergy coefficient of performance, i.e. COPEn and COPEx, respectively, obtained for system 2 have a drastic increment relative to system 1. Moreover, outcomes identify system 2 as a more economic system due to its low total product cost rate ( C ̇ P, tot ) at which m ̇ 1 with 20.95% decrement of C ̇ P, tot has a significant positive effect. Further results show that the environmental impact is improved by applying system 2 so that the total product environmental impact rate associated with exergy ( B ̇ P, tot ) for m ̇ 1, T3, T6 and T11 decreases within 21.52%, 10.59%, 8.96% and 8.35% respectively, as compared with system 1.